Marked Facial Weakness, Ptosis, and Hanging Jaw: A Case with RYR1-Related Congenital Centronuclear Myopathy - Singanamalla, Bhanudeep; Kesavan, Shivan; Aggarwal, Divya; Chatterjee, Debajyoti; Urtizberea, Andoni; Suthar, Renu (Journal of Pediatric Genetics, 2021)
Congenital myopathies are an expanding spectrum of neuromuscular disorders with early infantile or childhood onset hypotonia and slowly or nonprogressive skeletal muscle weakness. RYR1-related myopathies are the most common and frequently diagnosed class of congenital myopathies. Malignant hyperthermia susceptibility and central core disease are autosomal dominant or de novo RYR1 disorder, whereas multiminicore, congenital fiber type disproportion and centronuclear myopathy are autosomal recessive RYR1 disorders. The presence of ptosis, ophthalmoparesis, facial, and proximal muscles weakness, with the presence of dusty cores and multiple internal nuclei on muscle biopsy are clues to the diagnosis. We describe an 18-year-old male, who presented with early infantile onset ptosis, ophthalmoplegia, myopathic facies, hanging lower jaw, and proximal muscle weakness confirmed as an RYR1-related congenital centronuclear myopathy on genetic analysis and muscle biopsy.
Keywords: myopathy; ophthalmoplegia; centronuclear